The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.eujim.2019.100945
|View full text |Cite
|
Sign up to set email alerts
|

The use of pattern differentiation in WHO-registered traditional Chinese medicine trials – A systematic review

Abstract: Introduction: Pattern differentiation is a critical component for traditional Chinese medicine (TCM) diagnosis and treatment. However, the issue of whether pattern differentiation is appropriately applied in TCM interventional trials, including Chinese herbal medicine (CHM) interventions and non-herbal TCM interventions, is unclear. The aim of this study was to i) systematically review the current status of pattern differentiation used in WHO-registered clinical trials for different types of TCM interventions;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 24 publications
(25 reference statements)
0
22
0
Order By: Relevance
“…In our previous study, among 2955 TCM interventional trials that registered from 2003 to 2017, there are 376 (12.7%) trials that included the TCM pattern [ 37 ] . In TCM clinical practice, accurate TCM pattern differentiation is vital for the determination of TCM treatment [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, among 2955 TCM interventional trials that registered from 2003 to 2017, there are 376 (12.7%) trials that included the TCM pattern [ 37 ] . In TCM clinical practice, accurate TCM pattern differentiation is vital for the determination of TCM treatment [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, in our previous study, we found that among 376 TCM trial registrations that included Pattern(s) for participants, only 27 (7.2%) trials reported the diagnostic criteria for the Pattern studied. Furthermore, 61 (16.2%) trials did not provide the specific name of the Pattern studied [37]. Such vagueness prevents readers from properly interpreting results and reproducing the study.…”
Section: B Descriptions Of Control Group(s)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our previous study, we found that among 376 TCM trial registrations that included Pattern(s) for participants, only 27 (7.2%) trials reported the diagnostic criteria for the Pattern studied. Furthermore, 61 (16.2%) trials did not provide the speci c name of the Pattern studied [37]. Such vagueness prevents readers from properly interpreting results and reproducing the study.…”
Section: Item 14: Key Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…In our previous study, among 2,955 TCM interventional trials that registered from 2003 to 2017, there are 376 (12.7%) trials that included the TCM pattern [37]. In TCM clinical practice, accurate TCM pattern differentiation is vital for the determination of TCM treatment [38].…”
Section: Highlights Of Who Trds-tcmmentioning
confidence: 99%